PEPDar: A randomized prospective noninferiority study of ritonavir‐boosted darunavir for HIV post‐exposure prophylaxis - Faetkenheuer, G.; Jessen, H.; Stoehr, A.; Jung, N.; Jessen, A. B.; Kuemmerle, T.; Berger, M.; Bogner, J. R.; Spinner, C. D.; Stephan, C.; Degen, O.; Vogelmann, R.; et al. (HIV Medicine, 2016)
Objectives PEPDar compared the tolerability and safety of ritonavir‐boosted darunavir (DRV/r)‐based post‐exposure prophylaxis (PEP) with the tolerability and safety of standard of care (SOC). The primary endpoint was the early discontinuation rate among the per‐protocol population. Methods PEPDar was an open‐label, randomized, multicentre, prospective, noninferiority safety study. Subjects were stratified by type of event (occupational vs. nonoccupational, i.e. sexual) and were randomized to receive DRV/r plus two nucleoside reverse transcriptase inhibitors (NRTIs) or SOC PEP. Twenty‐two private or university HIV clinics in Germany participated. Subjects were ≥ 18 years old and had documented or potential HIV exposure and indication for HIV PEP. They initiated PEP not later than 72 h after the event and were HIV negative. Results A total of 324 subjects were screened, the per‐protocol population was 305, and 273 subjects completed the study. One hundred and fifty‐five subjects received DRV/r‐based PEP and 150 subjects received ritonavir‐boosted lopinavir (LPV/r)‐based PEP for 28–30 days; 298 subjects also received tenofovir/emtricitabine. The early discontinuation rate in the DRV/r arm was 6.5% compared with 10.0% in the SOC arm (P = 0.243). Adverse drug reactions (ADRs) were reported in 68% of DRV/r subjects and 75% of SOC subjects (P = 0.169). Fewer DRV/r subjects (16.1%) had at least one grade 2 or 3 ADR compared with SOC subjects (29.3%) (P = 0.006). All grades of diarrhoea, nausea, and sleep disorders were significantly less frequent with DRV/r, while headache was significantly more frequent. No HIV seroconversion was reported during follow‐up. Conclusions Noninferiority of DRV/r to SOC was demonstrated. DRV/r should be included as a standard component of recommended regimens in PEP guidelines.